MORPHOLOGICAL PROCESSES IN THE NAMES OF TRADITIONAL SURAKARTA CULINARY IN INSTAGRAM HASHTAGS DATA - Titik Akiriningsih; Dian Muhammad Rifai (Indonesian EFL Journal, 2026)
This research analyzes the morphological procedures used in forming the names of traditional Surakarta culinary items as represented in Instagram hashtags. Using a qualitative descriptive approach, data were collected from popular Instagram posts containing hashtags of traditional Surakarta foods. The data were analyzed based on Soeparno’s (2003) theory of morphological procedures. The results reveal two morphological procedures: duplication/reduplication and compounding. Among these, compounding is the most dominant type, accounting for 92,5% (25) data, while duplication/reduplication accounts for 7,5% (2) data. Examples such as gado-gado, arem-arem, cabuk rambak, and sate kere illustrate these morphological patterns. The prevalence of compounding suggests that social media users creatively combine free morphemes to produce meaningful culinary names that reflect both linguistic processes and local cultural identity. This study demonstrates how traditional culinary vocabulary continues to develop and spread through digital communication, highlighting the dynamic relationship between language, culture, and technology.